A thousand ways to understand happiness in the economy of the european union’s “next generation” funds a comprehensive vision under the lens of social marketing, history and happiness management - Ravina-Ripoll, Rafael; Galván Vela, Esthela; Galiano-Coronil, Araceli (My University, 2022)
In the era of the European Union’s Next Generation funds, there is little academic work that empirically explores the happiness management-social marketing construct from the perspective of the strategic management of organizations. The multidisciplinary study of this binomial can be very attractive for building the virtuous circle of happiness within corporations. This requires, on the one hand, the implementation of a culture based on the subjective well-being of their human capital, and on the other hand, changing the behaviour of their customers towards the adage of consumer happiness. The latter will be achieved by industries that set the train of tomorrow’s economic development on guiding principles other than materialism, low cost or irrational consumption. From what has been read so far, the authors of this chapter have carried out a bibliometric study of the dimensions of happiness management and social marketing, as well as their corresponding links. The empirical results of this analysis show, in an experimental phase, that the scientific works written in the last years of the 21st century on the attractive link between happiness management and social marketing are in an emerging stage of the literature. This fact hints at the long academic journey of holistic exploration of this construct in the disciplines of business organization and marketing. To fill this gap in the literature, future research should highlight the need for companies to implement policies that address their competitive and sustainable growth through happiness management and social marketing.
CAPITULO 1: What does happiness teach us in the next generation era: a bibliometric review of the happiness management and social marketing constructs
Keywords: Happiness and well-being; Economic; Social and artistic; Campus Tijuana